Using fractured outcrops to calculate permeability tensors: implications for geothermal fluid flow and the influence of seismic-scale faults - Smith, Ruaridh; Lesueur, Martin; Kelka, Ulrich; Poulet, Thomas; Köhn, Daniel (Geological Magazine, 2022)
Faulted and fractured systems form a critical component of fluid flow, especially within low-permeable reservoirs. Therefore, developing suitable methodologies for acquiring structural data and simulating flow through fractured media is vital to improve efficiency and reduce uncertainties in modelling the subsurface. Outcrop analogues provide excellent areas for the analysis and characterization of fractures within the reservoir rocks where subsurface data are limited. Variation in fracture arrangement, distribution and connectivity can be obtained from 2D fractured cliff sections and pavements. These sections can then be used for efficient discretization and homogenization techniques to obtain reliable predictions on permeability distributions in the geothermal reservoirs. Fracture network anisotropy in the Malm reservoir unit is assessed using detailed structural analysis and numerical homogenization of outcrop analogues from an open pit quarry within the Franconian Basin, Germany. Several events are recorded in the fracture networks from the Late Jurassic the Alpine Orogeny and are observed to be influenced by the Kulmbach Fault nearby with a reverse throw of 800 m. The fractured outcrops are digitized for fluid flow simulations and homogenization to determine the permeability tensors of the networks. The tensors show differences in fluid transport direction where fracture permeability is controlled by orientation compared to a constant value. As a result, it is observed that the orientation of the tensor is influenced by the Kulmbach Fault, and therefore faults within the reservoirs at depth should be considered as important controls on the fracture flow of the geothermal system.
CRIS-Team WoS Importer:2022-06-10
Keywords: natural fractures; geothermal; numerical modelling; fluid flow; outcrop; permeability tensors